Komunitas Fujoshi Di Kalangan Perempuan Indonesia - Putri Andam Dewi (Bina Nusantara University, 2012)
This article discusses fan community of the Boys Love (BL) manga among young women in Indonesia. BL manga tells a romance between fellow men. BL manga is a sub genre of shojo manga, the manga for girls and women readers in Japan. BL manga belongs to the genre for female readers because the comic artist is a woman. Both in Japan and outside Japan, the development of BL manga receives much attention from many researchers and observers of Japanese study. Using cultural-study perspective, they examine the phenomenon of BL manga and fujoshi community formed by BL fandom. This study discusses the formation of BL manga fandom community by linking the construction of gender identity using a cultural-study perspective and gender performativity concept by Judith Butler. By using Judith Butler's concept of gender performativity we can see why and how the Indonesian female teens construct their gender identity through fandom of BL manga.